The Decision Factors of Rural Part-Time Workers in Southeast Sulawesi: Characteristics and Determinants - Wa Ode Hasmayuli; Samsu Arif; Madris (Jurnal Ilmiah Membangun Desa dan Pertanian, 2022)
This study aimed to analyze the characteristics and determinants of rural part-time workers in Southeast Sulawesi Province. This study focuses on the socio-demographic attribute that can influence a person to become a part-time worker. Part-time workers are part of non-full workers, which is considered not a problem. Part-time workers are absorbed in less decent jobs. Young age groups dominate them because they are less experienced in the complexities of job search, less intense in wage negotiations, less financially secure, and more vulnerable to psychological stress. Part-time workers are those who work below standard hours but are not looking for work and are not available for work. This study uses secondary data from the August 2021 National Labor Force Survey (Sakernas). Samples used in this study were 3,540 part-time workers spread throughout Southeast Sulawesi Province. Two thousand eight hundred six part-time workers are in rural areas, and 734 are in urban areas. In this study, the dependent variable is part-time workers. While the variables of age, gender, position in the household, marital status, education level, and field of business are independent. The analytical method used in this study is binary logistic regression. This study shows the characteristics of rural part-time workers are dominated by those of the primary working age, female, ordinary household members, married, low education, and working in the agricultural sector. Based on the determinants, part-time workers are more likely to occur in those of young working age, have ever-married status, those with middle and low education, and work in the agricultural sector. Efforts are needed to reduce part-time workers to improve their welfare.